Mechanical Properties and Constitutive Model of Geopolymer Lightweight Aggregate Concrete - Peng Ren; Weijie Zhang; Xiaopeng Ye; Xi Liu (Buildings)
In order to study the mechanical properties and stress–strain relationship of geopolymer lightweight aggregate concrete (GLAC), 13 groups of different mix proportions were designed. The influence of the binder ratio, alkali–binder ratio, alkali activator modulus, steel fiber volume content, coarse aggregate volume content, and water–binder ratio on the cube compressive strength, splitting tensile strength, flexural strength and axial compression performance of GLAC was analyzed. The failure process and characteristics of GLAC under axial compression were analyzed, the stress–strain curve of GLAC was obtained, and the calculation model for characteristic points and the piecewise constitutive model of GLAC are proposed. The results show that GLAC has the characteristics of being lightweight and having early strength. The dry apparent density of the prepared concrete is within the range of 1712–1902 kg/m3. The cube compressive strength at 3 days and 7 days can reach 45–85% and 66–98% of the 28-day compressive strength, respectively. The mechanical properties of GLAC increase with the increase of slag content, alkali–binder ratio, and steel fiber volume content, and decrease with the increase of the alkali activator modulus and the coarse aggregate volume content. Moreover, both overly high and overly low water–binder ratios will reduce the strength of GLAC. The failure mode of GLAC is aggregate fracture failure. Incorporating steel fibers can effectively improve the failure mode of the concrete. The proposed calculation model for characteristic points and the constitutive model can predict the axial compression behavior of GLAC relatively accurately.